Differences in the Loin Tenderness of Iberian Pigs Explained through Dissimilarities in Their Transcriptome Expression Profile - Miguel Ángel Fernández-Barroso; Carmen Caraballo; Luis Silió; Carmen Rodríguez; Yolanda Nuñez; Fernando Sánchez-Esquiliche; Gema Matos; Juan María García-Casco; María Muñoz (Animals, 2020)
Tenderness is one of the most important meat quality traits and it can be measured through shear force with the Warner–Bratzler test. In the current study, we use the RNA-seq technique to analyze the transcriptome of Longissimus dorsi (LD) muscle in two groups of Iberian pigs (Tough and Tender) divergent for shear force breeding values. We identified 200 annotated differentially expressed genes (DEGs) and 245 newly predicted isoforms. The RNAseq expression results of 10 genes were validated with quantitative PCR (qPCR). Functional analyses showed an enrichment of DE genes in biological processes related to proteolysis (CTSC, RHOD, MYH8, ACTC1, GADD45B, CASQ2, CHRNA9 and ANKRD1), skeletal muscle tissue development (ANKRD1, DMD, FOS and MSTN), lipid metabolism (FABP3 and PPARGC1A) and collagen metabolism (COL14A1). The upstream analysis revealed a total of 11 transcription regulatory factors that could regulate the expression of some DEGs. Among them, IGF1, VGLL3 and PPARG can be highlighted since they regulate the expression of genes involved in biological pathways that could affect tenderness. The experiment revealed a set of candidate genes and regulatory factors suggestive to search polymorphisms that could be incorporated in a breeding program for improving meat tenderness.